Tubuloid differentiation to model the human distal nephron and collecting duct in health and disease - Fjodor A. Yousef Yengej; Carla Pou Casellas; Carola M.E. Ammerlaan; Charlotte J.A. Olde Hanhof; Emre Dilmen; Joep Beumer; Harry Begthel; Elise M.G. Meeder; Joost G. Hoenderop; Maarten B. Rookmaaker; Marianne C. Verhaar; Hans Clevers (Cell Reports, 2024)
Summary: Organoid technology is rapidly gaining ground for studies on organ (patho)physiology. Tubuloids are long-term expanding organoids grown from adult kidney tissue or urine. The progenitor state of expanding tubuloids comes at the expense of differentiation. Here, we differentiate tubuloids to model the distal nephron and collecting ducts, essential functional parts of the kidney. Differentiation suppresses progenitor traits and upregulates genes required for function. A single-cell atlas reveals that differentiation predominantly generates thick ascending limb and principal cells. Differentiated human tubuloids express luminal NKCC2 and ENaC capable of diuretic-inhibitable electrolyte uptake and enable disease modeling as demonstrated by a lithium-induced tubulopathy model. Lithium causes hallmark AQP2 loss, induces proliferation, and upregulates inflammatory mediators, as seen in vivo. Lithium also suppresses electrolyte transport in multiple segments. In conclusion, this tubuloid model enables modeling of the human distal nephron and collecting duct in health and disease and provides opportunities to develop improved therapies.